The relationship between red blood cell distribution width at admission and post-stroke fatigue in the acute phase of acute ischemic stroke - Peng, Meidi; Chen, Yupei; Chen, Yan; Feng, Koulan; Shen, Haiyan; Huang, Hongtao; Zhao, Wenxuan; Zou, Hua; Ji, Jianan (Frontiers in Neurology, 2022)
Introduction Post-stroke fatigue (PSF) is a common complication in the patients with acute ischemic stroke (AIS). This prospective study aimed to investigate the relationship between red blood cell distribution width (RDW) at admission and PSF in the acute phase. Methods The AIS patients were enrolled in Nantong Third People's Hospital, consecutively. PSF in the acute phase was scored according to the Fatigue Severity Scale. Levels of RDW were measured at admission. The associations were analyzed using multivariate regression and restricted cubic splines (RCS). Results From April 2021 to March 2022, a total of 206 AIS patients (mean age, 69.3 ± 10.7 years; 52.9% men) were recruited. After the adjustment for potential confounding factors, RDW at admission remained the independent associated factor with PSF in the acute phase (OR [odds ratio], 1.635; 95% CI [confidence interval], 1.153–2.318; P = 0.006). The linear dose-response associations of RDW with PSF in the acute phase were found, based on the RCS model (P for non-linearity = 0.372; P for linearity = 0.037). These results remained significant in other models. Conclusions RDW at admission could serve as a novel biomarker of PSF in the acute phase of AIS.